A RARE CASE OF BILATERAL SPONTANEOUS TENSION PNEUMOTHORAX IN A PATIENT WITH MUCORMYCOSIS - Sana, Mahreen; Anwar, Maha (Infectious Diseases Journal of Pakistan, 2023)
Mucormycosis is an invasive fungal infection seen in immunocompromised hosts. Here a rare case of mucormycosis with pulmonary involvement followed by bilateral spontaneous tension pneumothorax is described. Bilateral spontaneous tension pneumothorax is a rare and fatal condition. We present a case of 3 years old child, diagnosed case of acute Leukemia. During the course of induction chemotherapy, he was hospitalized with fever and diarrhea. He was being managed on lines of neutropenic colitis. During the hospital stay, the child developed sudden respiratory distress and seizures. Chest X-ray showed bilateral spontaneous tension pneumothorax. Immediate bilateral chest tubes insertions were done. He was also electively intubated. After successful lung expansion, the trial of weaning off the ventilator was given and patient was successfully extubated. CT Thorax after lung re-expansion showed few pneumatoceles with no bronchopleural fistulous communication. CT Brain and para nasal sinuses showed fungal rhinosinusitis with intracranial extension. Nasal endoscopy and debridement of necrotic tissue was done. Tissue cultures showed the growth of mucor species. The patient was also started on amphotericin B that was later changed to Posaconazole. He responded well to anti-fungal treatment and there was no recurrence of pneumothorax. Keywords: Mucormycosis, Tension pneumothorax, Bronchopulmonary fistula